The Impact of CPR Position (Kneeling, Footstool and Standing Beside Bed) on Cardiopulmonary Resuscitation Quality: A Literature Review - Ristina Mirwanti; M Reza Saputra; Wina Supriatna; Raissa Fatimah; Yupira Dera Sopyanti; Risma Dwiriyanti; Nancy Veronica; Jemi Rahmani Abdullah; Irma Mawarni Putri; Iduliah Fitriani (Universitas Padjadjaran, 2020)
Background: Cardiopulmonary Resuscitation (CPR) is one of the measures to deal with emergency cardiac arrest (cardiac arrest) where the heart organ loses its function suddenly. Hence it is unable to pump blood throughout the body. CPR consists of aid in circulation (compression) and breathing (ventilation). AHA has determined guidelines for implementing CPR, especially an essential point in CPR, namely chest compression. The standing position is fundamental in the implementation of CPR, but kneeling and footstool positions can be carried out during CPR implementation. This paper aims to show the impact of standing, kneeling, and footstool positions on CPR quality.Method: The method used is by searching journals in Science Direct, PubMed, and Google Scholar. The keywords used are CPR, Kneeling Position, Footstool, standing beside the bed Obtained eight selected journals according to the topic, then analyzed.Results: Based on the search result, eight articles meet the criteria. The literature review results showed three positions that can be chosen when conducting CPR: standing, kneeling, and footstool. Those positions could give impact toward helper: pain level and exhaustion degree, and quality of CPR: compression strength, depth of compression, amount of compression, chest recoil, elbow movement, and movement in the lower back.Conclusion: Three CPR positions can be done, including standing beside the bed, kneeling, and standing on stepstool footing. Each position gives impacts both to helper condition and CPR quality. Researchers recommend standing on stepstool footing due to it provides the best effect on CPR quality.